Implementation of Supplementary Water Irrigation and Rice Husk for Climate Change Adaptation and Improving Soil Quality in Dry Land, Gunungkidul - Riyanto Damasus; Budiarti Sri Wahyuni; Jihad Muhammad; Yustisia; Khairullah Izhar; Widowati Rahayu (E3S Web of Conferences, 2023)
Dry land in Gunungkidul is the land that depends on rainfall as the main water source to the crops. This research aimed to evaluate the implementation of supplementary water irrigation and rice husk for improving soil quality. The study conducted at dry land of Wonosari-Gunungkidul on June-Sept 2019. Experimental Design used Randomized Completely Block and replicated four times. The treatments were frequency of irrigation, namely F1 (1 times), F2 (2 times), F3 (3 times) a week, and application of soil amendment, namely: M1 (without mulch), M2 rice straw 4 ton.ha-1), M3 (rice husks 4 ton.ha-1), M4 (straw mulch + rice husk 4 ton.ha-1). The result of study showed that applying straw much and rice husk plus supplementary water irrigation two times a week was able to provide the highest corn production (7.46 ton.ha-1) and was not significantly different to the irrigation three times a week and showed an increased yield of corn 52.56% compared to control (watering once a week and without mulch/rice husk). Applying straw and rice husk can be improved the chemical soil properties (increasing water holding capacity,C-organic, P and K available and CEC).The financial farming of BC ratio reached 2.25 and increased 144.56% compare to control treatment.